The influences of furniture on childrens health and well-being at primary school - Valikhani, Mahkameh; Ibrahim, Rahinah; Dolah, Mohd Shahrizal (Penerbit Universiti Teknologi Malaysia, 2016)
Pre-schools and primary schools play a prominent role in the lives of children. In this phase of their life, reading and writing would begin. There are studies which explored the relationships between writing and reading performance and furniture in the classroom. A considerable body of research addresses the role of school furniture on children’s health. Nevertheless, the impact of furniture on behaviour received fairly insufficient attention in design and furniture industries. Since children have no choice in selecting their furniture, they ended becoming passive users in the design process. In this paper, we aim to understand the impacts that school furniture have on children’s health and performance. This paper reviews previous studies about children’s furniture at educational centers in order to introduce a new prototype of school furniture. This study could inform designers and those involved in children related educational systems to develop better furniture designs in schools.